Latent tuberculosis infection treatment completion in Biscay: differences between regimens and monitoring approaches - Ortiz Laza, N.; Lopez Aranaga, I.; Toral Andres, J.; Toja Uriarte, B.; Santos Zorrozua, B.; Altube Urrengoechea, L.; Garros Garay, J.; Tabernero Huguet, E. (Frontiers in Medicine, 2023)
Contact tracing and treatment of latent tuberculosis infection (LTBI) is a key element of tuberculosis (TB) control in low TB incidence countries. A TB control and prevention program has been active in the Basque Country since 2003, including the development of the nurse case manager role and a unified electronic record. Three World Health Organization-approved LTBI regimens have been used: isoniazid for 6 months (6H), rifampicin for 4 months (4R), and isoniazid and rifampicin for 3 months (3HR). Centralized follow-up by a TB nurse case manager started in January 2016, with regular telephone follow-up, telemonitoring of blood test results, and monitoring of adherence by electronic review of drugs dispensed in pharmacies. Objective: To estimate LTBI treatment completion and toxicity of different preventive treatment regimens in a real-world setting. Secondary objective: to investigate the adherence to different approaches to preventive treatment monitoring Methods: A multicentre retrospective cohort study was conducted using data collected prospectively on contacts of patients with TB in five hospitals in Biscay from 2003 to 2022. Results A total of 3066 contacts with LTBI were included. The overall completion rate was 66.8%; 86.5% of patients on 3HR (n=699) completed treatment vs 68.3% (n=1260) of those on 6H (p<0.0001). The rate of toxicity was 3.8%, without significant differences between the regimens. A total of 394 contacts were monitored by a TB nurse case manager. In these patients, the completion rate was 85% vs 67% in those under standard care (p<0.001). A multivariate logistic regression model identified three independent factors associated with treatment completion: being female, the 3HR regimen, and nurse telemonitoring. Conclusions 3HR was well tolerated and associated with a higher rate of treatment completion. Patients with nurse telemonitoring follow-up had better completion rates.